2007
DOI: 10.1089/cap.2006.0101
|View full text |Cite
|
Sign up to set email alerts
|

Once-Daily Multilayer-Release Methylphenidate in a Double-Blind, Crossover Comparison to Immediate-Release Methylphenidate in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Of the 90 enrolled patients, aged 6.4-17.5 years, 79 (88%) completed the study. Stable daily doses were 32.0 and 32.5 mg for MLR and IR-MPH, respectively. All efficacy parameters were significantly improved from baseline. A total of 73.2% and 81.0% of patients on MLR and IR-MPH were rated as "much" or "very much improved" on the CGI. A total of 77.4% and 81.1% of patients were normalized on the CPRS-R and 78.9 and 90.4% of patients were normalized on the CTRS-R for MLR and IR-MPH, respectively. The mean CASE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
(26 reference statements)
3
15
0
Order By: Relevance
“…MPH release was prolonged in the MLR formulation, as evidenced by the higher plasma concentrations between 10 and 12 hours. These findings were confirmed in a single dose pharmacokinetic study in children with ADHD (Quinn et al, 2007). A comparison of the pharmacokinetics of MLR MPH and Concerta ® showed higher plasma levels of methylphenidate in the first eight hours following dosing with MLR MPH, while maintaining comparable levels for the remainder of the day (Reiz et al 2008) The purpose of this study was to evaluate the comparative efficacy and pharmacodynamics of once-daily MLR MPH and IR MPH (Ritalin ® ) in a randomized, double-blind, three-way crossover, placebo-controlled study in children with ADHD.…”
Section: Introduction Isupporting
confidence: 63%
See 1 more Smart Citation
“…MPH release was prolonged in the MLR formulation, as evidenced by the higher plasma concentrations between 10 and 12 hours. These findings were confirmed in a single dose pharmacokinetic study in children with ADHD (Quinn et al, 2007). A comparison of the pharmacokinetics of MLR MPH and Concerta ® showed higher plasma levels of methylphenidate in the first eight hours following dosing with MLR MPH, while maintaining comparable levels for the remainder of the day (Reiz et al 2008) The purpose of this study was to evaluate the comparative efficacy and pharmacodynamics of once-daily MLR MPH and IR MPH (Ritalin ® ) in a randomized, double-blind, three-way crossover, placebo-controlled study in children with ADHD.…”
Section: Introduction Isupporting
confidence: 63%
“…The multilayer release (MLR) bead formulation of MPH (Biphentin ® ) that was evaluated in this study was designed to provide both a rapid initial release of MPH (40% of the total MPH) followed by a delayed and more prolonged phase of release, resulting in a biphasic concentration-time profile that has been found to be effective in the treatment of child, adolescent, and adult ADHD Weiss et al 2007). In a single-dose pharmacokinetic study of healthy adult volunteers, this MLR formulation was fully bioavailable, relative to the immediate release (IR) formulation under fasted and fed conditions (Purdue Pharma 2006).…”
Section: Introduction Imentioning
confidence: 99%
“…16–22 24 25 Most studies used both parent and teacher reports to assess symptoms, except Steele et al , who used only parent reports, and Dopfner et al , who used only teacher reports (figure 2). 19 22 The study results of Dopfner et al could not be included in the meta-analysis since the study was conducted over a single day.…”
Section: Resultsmentioning
confidence: 99%
“…After morning administration of MPH-MLR, a small drop in plasma MPH concentration occurs *4 hours postdosing, followed by a gradual increase in MPH concentrations, producing a second attenuated peak at *7 hours after dosing and then a gradual decline throughout the evening and nighttime hours (Adjei et al 2014a,b). Phase 2 studies of MPH-MLR in children, adolescents, and adults across a variety of settings demonstrated that once-daily administration produces significant improvements in behavioral and cognitive measures Weiss et al 2007;Schachar et al 2008). The MPH-MLR capsule is ingested orally or opened for its contents to be sprinkled on food; the two administration modes are bioequivalent (Adjei et al 2014b).…”
Section: Introductionmentioning
confidence: 99%